1977
DOI: 10.1111/j.1600-0722.1977.tb02111.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary fluoride and calcium concentrations, and their relationship to the secretion of saliva and caries experience

Abstract: ABSTRACT— Samples were collected from the stimulated saliva of 113 students enrolled in institutions of higher education. The students were divided into three “carries‐diagnostic groups” on the basis of indications given by the Dentocult® saliva test, which shows the frequency of lactobacilli and other aciduric microorganisms in saliva. The frequency of such microorganisms in 1 ml saliva in Group A was ≤ 103, in Group B > 103, < 104 and in Group C ≥104. The rate of secretion of saliva in Group A was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
1
1

Year Published

1980
1980
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
1
1
1
Order By: Relevance
“…Furthermore, Shaw et al [77] found a significantly higher average phosphate concentration in submaxillary-sublingual saliva from a group of caries-free children than in saliva from a group with high caries, although they found no difference for salivary calcium. In partial contrast, studies reported by Mandel [78] on salivary calcium and phosphate and by Turtola [79] on salivary calcium showed no significant differences between caries-free and caries-active groups. A few authors have investigated the possible association between calcium and phosphorus levels in plaque and caries, and obtained reasonably consistent findings.…”
Section: Calcium and Phosphatecontrasting
confidence: 56%
“…Furthermore, Shaw et al [77] found a significantly higher average phosphate concentration in submaxillary-sublingual saliva from a group of caries-free children than in saliva from a group with high caries, although they found no difference for salivary calcium. In partial contrast, studies reported by Mandel [78] on salivary calcium and phosphate and by Turtola [79] on salivary calcium showed no significant differences between caries-free and caries-active groups. A few authors have investigated the possible association between calcium and phosphorus levels in plaque and caries, and obtained reasonably consistent findings.…”
Section: Calcium and Phosphatecontrasting
confidence: 56%
“…This is in accordance with some previous findings [Mellberg and Larson, 1978;Schamschula et al, 1978;Turtola, 1977], In the study of Mellberg and Larson [1978] a strong caries challenge, i.e., cariogenic diet, enhanced fluoride uptake by en amel from fluoridated water in rats. This was explained by the fact that under the acidogenic conditions of a caries attack enamel becomes porous and acquires more fluoride than sound enamel.…”
Section: Discussionsupporting
confidence: 82%
“…They also found that the flow rate o f unstimulated but not o f stimulated saliva was significant ly related to sucrose clearance. A tendency has been found for individuals with low caries incidence to have a higher salivary flow rate than caries-active individuals [Ericsson ct al., 1954;Shannon and Terry, 1965;Kapsimalis et al, 1966;Turtola, 1977], The large effect of experimental dry mouth has been shown by Hase and Birkhed [1988], Among the several factors that influence the sugar clear ance, the unstimulated salivary flow is thought to be of ma jor importance, but also several other factors, such as the volumes of saliva in the mouth before and after swallowing, have been proposed to be important [Dawes. 1984;Lagerlof and Dawes, 1984].…”
Section: Discussionmentioning
confidence: 99%